Controversial diversity: diversity discourses and dilemmas among Swedish police recruits - Wieslander, Malin (Policing and society, 2020)
Diversity strategies to increase social inclusion in organisations have been a major concern in various institutions during recent decades. This article examines Swedish police recruits’ talk about diversity. The study is based on data from ethnographic fieldwork at the Swedish National Police Academy and focus group interviews of police recruits. Twenty-seven recruits were interviewed in their final year at the police academy, which included a period of probationary service at a police station. Using a discourse analysis, the article explores how the Swedish police's official policies for diversity and social equality are recognised, but also called into question, by Swedish police recruits. One dominating discourse of difference and two controversial discourses on diversity are outlined, showing that recruits frequently draw upon multiple discourses to legitimise their claims for and against diversity. A conceptual framework is developed for understanding the discourses and dilemmas of diversity within the police, with examples provided of how social order is reproduced among recruits.